Infecções graves em pacientes com artrite reumatoide expostos aos medicamentos biológicos: relevância e modificações da taxa com o tempo – dados de registros da américa do sul - Ranza, Roberto (2018)
Background: Most reports on serious infections (SI) in rheumatoid arthritis (RA) patients treated with biologic disease-modifying drugs (bDMARDs) are from the USA and Western Europe. Data from other regions are largely missing. We report data from two South American countries with different backgrounds and health-care systems with similar registries and definitions. Methods: We merged 2010-2016 data from two registries, BiobadaBrasil (Brazil) and BiobadaSAR (Argentina), which share the same protocol, online platform and data monitoring process. Patients with active RA were included in the registries when they began the first bDMARD or conventional synthetic DMARD (csDMARD). The SI incidence rate (IR) per 1000 p/y and adjusted IR ratio (aIRR) were estimated for bDMARDs and csDMARDs. Results: Data were analyzed for 3717 RA patients with an exposure of 13380 p/y. The 2591 patients treated with bDMARDs (64% treated with TNF antagonists) had an exposure of 9300 p/y, and the 1126 patients treated with csDMARDs (90% with methotrexate or leflunomide) had an exposure of 4081 p/y. The SI IR was 30.54 (CI 27.18-34.30) for all bDMARDs and 5.15 (CI 3.36-7.89) for sDMARDs. The aIRR between the two groups was 2.03 ([1.05, 3.9] p = 0.034) for the first six months of treatment but subsequently increased to 8.26 ([4.32,15.76] p<0.001). The SI IR for bDMARDs decreased over time in both registries, dropping from 36.59 (28.41-47.12) in 2012 to 7.27 (4.79-11.05) in 2016. Conclusion: While SI remains a major concern in South American patients with RA treated with bDMARDs, it is reducing favorably over time.